We start with the polynomial expression:
\[
25 z^{2} - 4 y^{2}
\]
Step 2: Recognize the Difference of Squares
The expression \(25 z^{2} - 4 y^{2}\) can be recognized as a difference of squares, which follows the formula:
\[
a^{2} - b^{2} = (a - b)(a + b)
\]
where \(a = 5z\) and \(b = 2y\).
Step 3: Apply the Difference of Squares Formula
Using the difference of squares formula, we can factor the polynomial:
\[
25 z^{2} - 4 y^{2} = (5z)^{2} - (2y)^{2} = (5z - 2y)(5z + 2y)
\]
Step 4: Present the Final Factorization
Thus, the fully factorized form of the polynomial is:
\[
(5z - 2y)(5z + 2y)
\]